2021
DOI: 10.1093/jscr/rjab389
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic laparoscopy and oophorectomy for ovarian vein thrombosis in a patient with COVID-19: a surgical case report and literature review

Abstract: Ovarian vein thrombosis (OVT) is a rare condition most frequently associated with pelvic inflammatory disease (PID), malignancy or the immediate postpartum period. This case study reports on a 56-year-old woman who developed OVT 11 days after a positive COVID-19 diagnosis. Imaging including abdominal/pelvic computed tomography, transvaginal Doppler ultrasound and transabdominal pelvic ultrasound failed to definitively diagnose the thrombotic etiology of the patient’s presentation. Ultimately, laparoscopic visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Symptomatic postpartum OVT occurs in 0.01-0.05% of deliveries, especially in C-sections [17]. In this review, no significant obstetric history was found in the majority of the cases (77.77%) [6,11,13,14,[18][19][20].…”
Section: Patient Demographicsmentioning
confidence: 68%
See 2 more Smart Citations
“…Symptomatic postpartum OVT occurs in 0.01-0.05% of deliveries, especially in C-sections [17]. In this review, no significant obstetric history was found in the majority of the cases (77.77%) [6,11,13,14,[18][19][20].…”
Section: Patient Demographicsmentioning
confidence: 68%
“…Our review corroborates a similar finding. A total of 66.66% of patients presented within the first two weeks after a COVID-positive test [11,13,[18][19][20][21]. The remaining 33.33% of patients took three to eight weeks for presentation [6,14].…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…An autopsy study by Wichmann et al reported microthrombi in the prostate of male patients [38] . In female COVID-19 patients, there were also reports of primary ovarian failure (POF) and ovarian vein thrombosis (OVT) [187] , [188] , [189] , [190] , [191] . One study reported POF due to long COVID-19 [192] , and another presented a case of OVT in a pregnant woman [193] .…”
Section: Introductionmentioning
confidence: 99%
“… 3 5 Recently, OVT has been associated with COVID 19 infection, presumably because of a hypercoagulable state caused by the virus. 6 , 7…”
Section: Introductionmentioning
confidence: 99%